Exploring the influence of wind, vegetation and water sources on the spread of forest fires in the Brazilian Cerrado Biome using Cellular Automata - Brasiel, Heitor C.; Lima, Danielli A. (Anais do Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos Naturais (WCAMA), 2023)
The fires in different Brazilian biomes have been increasingly frequent, leaving more and more consequences for the inhabitants, fauna, and flora of the affected region. Therefore, a computational model based on two-dimensional cellular automata was developed to simulate a real environment through software that predicts the behavior of the fire that starts at a predetermined location and spreads over a period of time. For the simulation, a mathematical-computational model based on cellular automata was developed in the Standard C Language, in which mathematical rules are given to order its evolution over time, generating more accurate results. Different scenarios were considered for the experiments, taking into account parameters such as combustion intensity, presence of wind, rivers, and homogeneous and heterogeneous vegetation. The results showed that these parameters can drastically affect the spread of the fire, with emphasis on the intensity of combustion in drier vegetation and the presence of water sources as a physical barrier.